Clinical manifestations of post-traumatic syndrome in combatants with eye trauma and partial vision loss - Adbrakhimov, R. A. (Journal of Education, Health and Sport, 2019)
Optic traumata are quite often found in the structure of modern combat trauma. Acquired as an adult, the loss of vision as a result of home accident injury entails the destruction of the victim’s usual life stereotype. In the case of partial loss of vision of the traumatic genesis due to injury in battle, the victim has the influence of powerful stress factors that affect the victim’s mental health. This is the phenomenon of mental maladjustment and it develops in response to participation in military actions and presents a powerful stress factor. In the work presented these are clinical manifestations of post-traumatic syndrome, which by their expressiveness and spectrum did not correspond to the diagnosis of post-traumatic disorder, which made it impossible to form such a clinical diagnosis. The interaction of these main factors, their influence upon one other, form complex of mental manifestations of somatic trauma. Therefore, there is a need to develop specialized, highly targeted approaches to medical and psychological rehabilitation of combatants with partial loss of vision of traumatic genesis against the background of clinical manifestations of post-traumatic syndrome. Neglect of any of these factors leads to ineffective rehabilitation work with this contingent. The objective: to study the phenomenology of psychological manifestations in combatants with optical injuries and partial loss of vision against the background of clinical manifestations of post-traumatic syndrome, and further determination of the targets for medical and psychological measures for their rehabilitation. Materials and methods. Under PIC conditions, 100 combatants were examined. 54 of them had optic injury and partial loss of vision on the background of clinical manifestations of post-traumatic syndrome; 46 had clinical manifestations of post-traumatic syndrome. 59 men with partial loss of vision as a result of home accident formed group of comparison. Results and discussion. In combatants with military optic trauma and partial loss of vision against the background of clinical manifestations of post-traumatic syndrome, the latter are dominant. The clinical symptoms of victims with a military optic injury against the background of clinical manifestations of post-traumatic syndrome reflect the structure of the manifestations of post-traumatic syndrome and demonstrate the direction of their formation against background of neurotic symptoms. The relevance of clinical symptoms in the subjects under study in its importance predominates over that which develops after home optic accident.